Report of the Fourth External Program and Management Review (EPMR) of the International Food Policy Research Institute (IFPRI) - Review Panel; Gardner, Bruce L.; Paul, Louis; Spencer, Dunstan; Svedberg, Peter; Valdés, Alberto; Zhang, Linxiu; Masaoka, Jan; Kelley, Timothy; Lantin, Manny; Ozgediz, Selçuk (Consultative Group on International Agricultural Research, 2006)
SC is pleased to note the overall positive performance of the Centre during the period under review. This is all the more impressive given the rapid increase in budget (from $20 million in 1998 to $34 million in 2004), with an increased share of restricted project funding, an expansion in the research and outreach portfolio with the incorporation of the ISNAR programme and initiation of the co-led Challenge Programme on Biofortification, and the major changes in the programmatic structure, including development of a new IFPRI Division covering development strategy and governance (DSGD). The Report provides a convincing case that IFPRI has indeed "moved with impression agility" in aligning its organization with the many changes in the external and internal environments over the last seven years.